Alih Kode Dalam Masyarakat Bajau domain Transaksi Jual Beli Di Kecamatan Pulau Laut Utara Kotabaru - Husni Mubarak (STKIP Paris Barantai, 2010)
This research aims to describe the form and the factors that determine the code switching in the sale and purchase transactions in the Bajau community. The method used in this research is a qualitative approach. The main data in this research are data derived from oral speech obtained through the recording, field notes, and interviews. The main instrument of this research is the researcher himself that is accompanied by field note, interview procedure, and recording and also accompanied by two men who acted as translator. The data analysis that is used in this research encompasses three steps. Those three steps are (1) data reduction, (2) presentation of data, (3) the conclusion/verification. The analysis was carried out during and after the data collected from those three steps until the final conclusion. To obtain the validity of the findings, the researcher does triangulation and cross check. Based on the result of the research found the following things (1) a form of code switching used by the Bajau community in the sale and purchase transaction is the language transition from BB to the BBj. In addition, a form of code switching in the form af a single variety of languages, namely BB. (2) code switching that is shown by the Bajau community turned out to just use a simple patern, namely BB + BB. This patern as a whole appears in a variety of speech discourse on the sale and purchase transactions. (3) code switching done by the Bajau community in the sale and purchase transactions are influenced by several factors, namely place and the situation of utterance, and also the intention to hide anything. Kata-kata Kunci: Alih Kode-Masyarakat Bajau-Transaksi Jual Beli